21. THE FACTORS RELATED TO ANOREXIC REALITY IN CHILDREN UNDER 5 YEARS OLD VISITED THE THAI NGUYEN GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine some factors related to children with anorexia who visited for examination of Thai Nguyen General Hospital.Materials and methods: A case-control study on 337 children from 6 months to 5 years old (151 children with anorexia, 186 children without anorexia), when the children's families visited for examination to Thai Nguyen General Hospital (from March, 2024 to October, 2024) and who met the sample criteria to be included in the sample, they were given a self-filled survey form.Results: The rate of anorexia in the 25-36 month group was 2.32 times higher; and children of 37-48 month group was 3.09 times higher than that of the non-anorexia group; the female group was 0.57 times higher than that of the male group; Anorexia in the group with other caregivers was 0.48 times higher than that of the group with mothers as the main caregivers; the rate of anorexia in the group of children who were breastfed for the first 6 months was 1.08 times lower than that of the other groups. However, the education level and occupation of the caregiver were not related to the rate of anorexia in children.Conclusions: To promote health education at medical facilities to advise mothers to practice breastfeeding in the first 6 months to limit the rate of anorexia in children < 5 years old.
Keywords: Anorexia; anorexia scale; children under 5 years old; Thai Nguyen General Hospital.